The Analysis of Oral Variety in Medan City - Ginting, Adelina (Kairos English Language Teaching Journal, 2021)
The research is aimed to describe the oral variety that is used by the people in Medan City. The location of this research was carried out in Medan City, Lingkungan II Titi Rantai Padang Bulan Medan. This study uses a qualitative method. Sources of data obtained from the visitors in 5 coffee shop in Lingkungan II Titi Rantai Padang Bulan. Results of the study showed the oral variety which is used in the form of abbreviations said among other things: Mandi, Nurdin , Martabe, the oral variety in the form of words that are influenced from the language of the area among others, bagudung, lalap, lateung, in addition to the many found the use of language phenomenon those are: Apheresis namely the removal of sound (phoneme) at the beginning of the word: saja - aja, Syncope namely removal of noise in the middle of the word: Tahu-tau, Haplology namely the removal of some phoneme in the middle of the word: Sedikit-dikit , Paragog namely the addition of sound at the end of words: Muka-mukak , Construction purposes, namely a combination of two pieces of words into a word: Bagai-Mana-Bagaimana, Monophothongization namely change two sounds vowels into one vowel: Sampe-sampai, Hypercorrection namely changing one phoneme into phoneme others: Pelit-celit